AVALIAÇÃO DA EFICIÊNCIA DO INDUTOR OVOPEL NA REPRODUÇÃO INDUZIDA DE LAMBARI (Astyanax lacustris) - TAVARES, Tainara Vieira; SANTOS, Jussara Garrido; LIMA, Andre Ferreira; AMARAL, Cristiane Meldau de Campos; WANDERLEY, Alysson Martins; COSTA, Deliane Cristina (ANAIS DO ENIC, 2024)
-